Comparative analysis of the interaction between alpha-lactalbumin and two edible azo colorants equipped with different sulfonyl group numbers. (1st August 2023) - Li, Mohan; Zhou, Dian; Wu, Di; Hu, Xia; Hu, Jie; Geng, Fang; Cheng, Lei
Graphical abstract: Highlights: Acid red 27 and acidic red B presented good affinity to bind to alpha-lactalbumin. Quenching mechanisms of acid red 27/acidic red B to alpha-lactalbumin mainly belong to static. Bindings were mainly driven by hydrophobic forces. Different association strengths differentially affect the alpha-lactalbumin conformation. Abstract: Alpha-lactalbumin ( α -La) is a crucial active component in whey protein. It would be mixed with edible azo pigments during processing. Spectroscopic analyses and computer simulations were used here to characterize the interaction between acid red 27 (C27) /acidic red B (FB) and α -La. Fluorescence, thermodynamics, and energy transfer showed the binding mechanism is a static quenching with a medium affinity. This binding process occurred spontaneously and was mainly driven by hydrophobic forces. Conformation analysis showed FB led to a greater change in the secondary structure of α -La compared with C27. C27 increased and FB decreased the surface hydrophobicity of α -La. The spatial structures of complexes were visualized with computer aid. The azo colorant binds to α -La easily and deeply with a smaller space volume and dipole moment and thereby affecting the α -La conformation and functionality. This study provides a theoretical basis for the application of edible azo pigments.